Motherhood and Mothering in Anglo-Saxon England - Dockray-Miller, M. author. aut Link
XIV, 161 p.
Keywords: Motherhood and Mothering in Anglo-Saxon England sifts through the historical evidence to describe and analyze a world of violence and intrigue, where mothers needed to devise their own systems to protect, nurture, and teach their children. Mary Dockray-Miller casts a maternal eye on Bede, the Anglo-Saxon Chronicle, and Beowulf to reveal mothers who created rituals, genealogies, and institutions for their children and themselves. Little-known historical figures - queens, abbesses, and other noblewomen - used their power in court and convent to provide education, medical care, and safety for their children, showing us that mothers of a thousand years ago and mothers of today had many of the same goals and aspirations.